Fundamentals of Membrane Bioreactors Materials, Systems and Membrane Fouling - Ladewig, Bradley; Al-Shaeli, Muayad Nadhim Zemam (Springer Transactions in Civil and Environmental Engineering,, 2017)
This book provides a critical, carefully researched, up-to-date summary of membranes for membrane bioreactors. It presents a comprehensive and self-contained outline of the fundamentals of membrane bioreactors, especially their relevance as an advanced water treatment technology. This outline helps to bring the technology to the readers' attention, and positions the critical topic of membrane fouling as one of the key impediments to its more widescale adoption. The target readership includes researchers and industrial practitioners with an interest in membrane bioreactors.